2002
DOI: 10.1155/2002/679683
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Dyspepsia: Implication for Empiric Therapy

Abstract: Dyspepsia describes a symptom complex thought to arise in the upper gastrointestinal tract and includes, in addition to epigastric pain or discomfort, symptoms such as heartburn, acid regurgitation, excessive burping or belching, a feeling of slow digestion, early satiety, nausea and bloating. Based on the evidence that heartburn cannot be reliably distinguished from other dyspeptic symptoms, the Rome definition appears to be too narrow and restrictive. It is particularly ill suited to the management of uninve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Hunt et al have suggested that patients with associated heartburn should be treated with proton-pump inhibitors (PPIs), which would relieve the patients' symptoms if they were suffering from GERD rather than dyspepsia. 17 If PPIs had no effect, this may suggest that the patients' upper abdominal symptoms were due to dyspepsia rather than GERD. This would, however, eliminate patients with dyspepsia, who may respond to acid inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Hunt et al have suggested that patients with associated heartburn should be treated with proton-pump inhibitors (PPIs), which would relieve the patients' symptoms if they were suffering from GERD rather than dyspepsia. 17 If PPIs had no effect, this may suggest that the patients' upper abdominal symptoms were due to dyspepsia rather than GERD. This would, however, eliminate patients with dyspepsia, who may respond to acid inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Dyspepsia is a condition comprising a complex of symptoms in the upper gastrointestinal tract which includes, in addition to epigastric pain or discomfort, symptoms, such as heartburn, acid regurgitation, excessive burping or belching, a feeling of slow digestion, early satiety, nausea and bloating (Talley et al, 1992;Hunt et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…16 In conclusion, we have shown that the magnitude of risk for gastric carcinoma and for gastric precancerous lesions increases with increasing number of EPIYA C motifs in the infecting H. pylori strains. Although the extent to which H. pylori eradication decreases the risk of gastric carcinoma is unknown and is still a controversial issue, 39,40 individuals infected with strains with higher-risk genotypes are most likely to benefit from H. pylori eradication, as such treatment could result in substantially reduced gastric carcinoma risk. Our results suggest that an intervention aimed at the 29% of individuals with gastritis and with the high-risk bacterial genotypes (i.e.…”
Section: Discussionmentioning
confidence: 99%